Kenali Sejak Dini, Lindungi Diri: Edukasi dan Praktik Pemeriksaan Payudara Sendiri (SADARI) pada Wanita Usia Subur di Kelurahan Tlogomulyo, Semarang - Meila Rahmawati K; Friska Realita; Azzurivia Reihana L (LPPM STIKES Madani, 2026)
Limited awareness and practical skills related to Breast Self-Examination (BSE) among women of reproductive age contribute to delays in the early detection of breast cancer. Health education plays an important role in strengthening community capacity and enabling women to recognize breast changes at an early stage. This community service program was conducted among 65 women of reproductive age in Tlogomulyo Village, Semarang City, through health education sessions, demonstrations using a breast model, and supervised BSE practice. The effectiveness of the program was assessed using a pretest-posttest design with questionnaires measuring participants' knowledge and attitudes. The mean knowledge score increased from 6.3 to 9.7, while the mean attitude score improved from 7.2 to 10. Statistical analysis revealed a significant difference between the pre-intervention and post-intervention scores (p < 0.05). In addition to the improvement in scores, participants were able to correctly demonstrate the BSE procedure. The combination of health education, demonstrations, and practical sessions significantly improved participants' knowledge, attitudes, and BSE skills, highlighting its value as a promotive and preventive strategy for supporting early breast cancer detection within the community.